Functional interrelationship between TFII‐I and E2F transcription factors at specific cell cycle gene loci. Issue 1 (31st July 2017) - Shen, Yong; Nar, Rukiye; Fan, Alex X.; Aryan, Mahmoud; Hossain, Mir A.; Gurumurthy, Aishwarya; Wassel, Paul C.; Tang, Ming; Lu, Jianrong; Strouboulis, John; Bungert, Jörg
Abstract: Transcription factor TFII‐I is a multifunctional protein implicated in the regulation of cell cycle and stress‐response genes. Previous studies have shown that a subset of TFII‐I associated genomic sites contained DNA‐binding motifs for E2F family transcription factors. We analyzed the co‐association of TFII‐I and E2Fs in more detail using bioinformatics, chromatin immunoprecipitation, and co‐immunoprecipitation experiments. The data show that TFII‐I interacts with E2F transcription factors. Furthermore, TFII‐I, E2F4, and E2F6 interact with DNA‐regulatory elements of several genes implicated in the regulation of the cell cycle, including DNMT1, HDAC1, CDKN1C, and CDC27 . Inhibition of TFII‐I expression led to a decrease in gene expression and in the association of E2F4 and E2F6 with these gene loci in human erythroleukemia K562 cells. Finally, TFII‐I deficiency reduced the proliferation of K562 cells and increased the sensitivity toward doxorubicin toxicity. The results uncover novel interactions between TFII‐I and E2Fs and suggest that TFII‐I mediates E2F function at specific cell cycle genes. Abstract : TFII‐I and E2F transcription factors have previously been shown to regulate genes involved in cell cycle regulation and stress response. We demonstrate that TFII‐I interacts with E2F transcription factors and that it mediates their association with specific cell cycle genes. Reduction of TFII‐I expression reduced expression of specific E2F occupied cell cycle genes and reduced proliferation of K562 cells.